Implementation of Problem-Based Learning (PBL) Model Assisted by Electronic IPA LKPD to Improve Critical Thinking Skills of 8th Grade Students - Sarawati, Tia; Zebua, Ester Novi Kurnia; Wiyatmo, Yusman (WaPFi (Wahana Pendidikan Fisika), 2025)
This study aims to: (1) measure the improvement in critical thinking skills of SMPN 3 Sumber students after implementing the Problem-Based Learning (PBL) model assisted by electronic LKPD; (2) determine whether there is a significant difference in the average score of critical thinking skills before and after the implementation; and (3) assess the effect size of the PBL model assisted by electronic LKPD in improving critical thinking skills. This pre-experimental study employed a One-Group Pretest-Posttest Design, with Class VIII-B students (n = 34) selected through purposive sampling. The research instrument was a critical thinking test, analyzed using descriptive and inferential statistics. The results revealed that: (1) the improvement in students’ critical thinking skills was categorized as moderate with an N-gain score of 0.54; (2) there was a significant difference in the average scores before and after implementation; and (3) the effect size of the PBL model was very large, with a value of 2.30. These findings demonstrate the effectiveness of the PBL model assisted by electronic LKPD in enhancing students' critical thinking skills.